Cyanogenic and non-cyanogenic glycosides from Manihot esculenta - Hunsa Prawat (2018)
In addition to lotaustralin and linamarin, a novel cyanogenic glycoside, 2-((6-O-(β-d-apiofuranosyl)-β-d-glucopyranosyl)oxy)-2-methylbu tanenitrile, two novel non-cyanogenic glycosides, (2S)-((6-O-(β-d-apiofuranosyl)-β-d-glucopyranosyl)oxy)butane and 2-((6-O-(β-d-apiofuranosyl)-β-d-glucopyranosyl)oxy)propane, and a simple non-cyanogenic glycoside, ethyl β-d-glucopyranoside, were isolated from an ethanolic extract of the fresh root cortex of Manihot esculenta. From a methanolic extract of the fresh leaves of this species lotaustralin and linamarin, and two flavonoid glycosides, kaempferol-3-O-rutinoside and quercetin-3-O-rutinoside were isolated. © 1995.